39.. A SURVEY ON STUDENT SATISFACTION WITH THE CONTINUING PHARMACEUTICAL EDUCATION COURSE IN ACCORDANCE WITH DECREE 54/2017/ND-CP (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the satisfaction of participants attending the continuing pharmaceutical education course in accordance with Decree 54/2017/ND-CP at Hai Duong Central College of Pharmacy; to identify associated factors; and to propose improvements to the program.Methods: A cross-sectional study was conducted among 133 participants from April to June 2025. The survey included 24 Likert-scale items (1-5 points) assessing satisfaction and 5 open-ended questions. Quantitative data were analyzed using Microsoft Excel and SPSS 26.0 (t-test, ANOVA), and qualitative responses were thematically categorized.Results: The overall satisfaction score was 4.24 ± 0.47 points, with the highest satisfaction reported in the lecturer domain (4.28 ± 0.49 points) and the lowest in facilities and infrastructure (4.18 ± 0.55 points). Content related to legal regulations and practical application in pharmaceutical practice received positive evaluations. There were no statistically significant associations between satisfaction and gender, professional title, or years of experience (p > 0.05). However, participants who attended multiple courses showed a trend toward higher satisfaction (p =  0,054). Suggestions for improvement included increasing course duration, adding topics on Pharmaceutical Law and antibiotics, and upgrading the online learning infrastructure.Conclusion: The continuing pharmaceutical education course at Hai Duong Central College of Pharmacy achieved a high level of satisfaction (4.24/5 points), particularly in terms of practical content and instructor quality. However, technical infrastructure and course duration need enhancement. The institution is recommended to incorporate additional topics such as Pharmaceutical Law, antibiotic stewardship, and pharmacy management, and to upgrade the e-learning platform to improve training quality and meet the requirements of Decree 54/2017/NĐ-CP, thereby supporting pharmacists more effectively.
Keywords: Satisfaction; continuing pharmaceutical education; Decree 54/2017/ND-CP.